SURVEI KEPUASAN DOSEN DAN TENAGA KEPENDIDIKAN TERHADAP PENGELOLAAN MANAJEMEN SDM TAHUN AJARAN 2021 / 2022 - Dedi Prayitno (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2023)
Consumers can experience one of three levels of general satisfaction, namely if performance is below expectations, consumers will feel disappointed, but if performance matches expectations, customers will feel satisfied and if performance exceeds expectations, customers will feel very satisfied, happy or happy. Service is a very important factor, especially for universities which in this case are engaged in services. Service to students is very important for the life of a university, because without students, the college will be closed. Thus, university service activities must be oriented to customer satisfaction, namely students. Maintaining satisfaction needs to be done to maintain positive attitudes of students as service users while minimizing negative attitudes that can be caused as a result of poor service quality. Management HR Management is in the category of satisfactory / Satisfied. Judging from the scores of each statement item, it appears that Lecturers and Educators are satisfied with all aspects and services of HR management carried out by the "YAB" Academy of Physiotherapy. In general, the level of satisfaction of Lecturers and Education Personnel is very good, but it is important for AKFIS YAB to continue to maintain and improve services to Lecturers and Educators by improving the performance of the services provided.